Design and Build a Quality Assurance Document Archiving Application Using the Rapid Application Development - Danang Rudy Purnomo; Inung Diah Kurniawati; Latjuba Sofyana STT (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
Higher Education quality assurance is a planned and sustainable process in systematically improving the quality of Higher Education. One of the functions of quality assurance for tertiary institutions is for accreditation activities, in study programs accreditation preparation is an activity that often requires time, energy and the minds of the academic community. The problem that often arises in quality assurance activities is that supporting data and information that are required for completeness have not been well documented. As time goes by, there are more and more documents and the search for documents is getting longer, because you have to open documents in every folder where these documents are not small. The purpose of this research is to overcome some of the problems that arise, including good archive management, documents can be grouped by year or criteria and time efficiency in recapitulating all quality assurance documents. The method used in the development of this system is the Rapid Application Development method, which enables faster system development. Document Archiving Information System for Website-Based Quality Assurance in Informatics Engineering Study Program, University of PGRI Madiun, was created using the Laravel framework, while databases used MySQL. The tools used in the process of making this system are XAMPP for the database server, Visual Studio Code for the text editor. In system testing using black box testing which only tests software functionality, the test shows valid results and no errors or bugs occur.